A Size Controlled Synthesis of Magnetite Nanoparticles in Pure Inorganic Medium - Ansari, M. Thameem (Asian Journal of Chemistry, 2016)
An extensive research has been carried out on the synthesis of magnetite nanoparticles by co-precipitation technique. Most of the co-precipitation technique shows the improper size and size distribution of the magnetite nanoparticles. In few reports organic stabilizers were employed to control the synthesis of magnetite nanoparticle. In this work, the pure inorganic precursors were employed for the synthesis of magnetite nanoparticles. The reports showed that pure form of magnetite nanoparticles with good size distribution. Hence this is the facile approach for the synthesis of magnetite nanoparticles; which can be employed for the various biomedicine applications.